2018
DOI: 10.1371/journal.pntd.0006540
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of dengue virus specific T cell responses and correlation with viral load and clinical disease severity in acute dengue infection

Abstract: BackgroundIn order to understand the role of dengue virus (DENV) specific T cell responses that associate with protection, we studied their frequency and phenotype in relation to clinical disease severity and resolution of viraemia in a large cohort of patients with varying severity of acute dengue infection.Methodology/Principal findingsUsing ex vivo IFNγ ELISpot assays we determined the frequency of dengue viral peptide (DENV)-NS3, NS1 and NS5 responsive T cells in 74 adult patients with acute dengue infecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 45 publications
4
35
0
Order By: Relevance
“…Presence of sustained levels of IFN-γ prior and early after DENV challenge in vaccinees has been associated with protection against viremia and/or severe disease 64,65 . We observed a similar phenotype of the polyfunctional response of CD8 + T cells prior DENV infection in animals with longer convalescence to ZIKV.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of sustained levels of IFN-γ prior and early after DENV challenge in vaccinees has been associated with protection against viremia and/or severe disease 64,65 . We observed a similar phenotype of the polyfunctional response of CD8 + T cells prior DENV infection in animals with longer convalescence to ZIKV.…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, we also found that the magnitude of the DENV-specific T-cell response inversely correlated with the degree of viraemia, further suggesting that T cells have a protective role in acute dengue. 11 Apart from the breadth and magnitude of a T-cell response, their functionality has also been shown to be crucial in protection against many infections. [12][13][14] Polyfunctional T cells that produce multiple types of cytokines have been shown to be protective and correlate with resolution of viraemia, especially in chronic viral infections.…”
Section: Introductionmentioning
confidence: 52%
“…Although we previously reported that IFNγ-producing T cells as determined by ex vivo ELISpot inversely correlated with the viraemia, we believe that we did not see a similar observation, as we only investigated CD8+ T cells in this study compared with the overall DENV-Tcell responses in our previous study. 11 In healthy individuals who were naturally exposed to the DENV, the majority of DENV-specific T cells produced two cytokines, irrespective whether they were simulated with conserved-or serotype-specific peptides. 7 However, we found that in acute infection only 18.1% to 23.3% of DENV-specific T cells produced two cytokines/ effectors, possibly due to the downregulation of T-cell receptor signaling pathways involved in cytokine during acute dengue.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the case of flaviviruses, it has recently become evident that distinct T cell populations, virus serotypes, sequence, and number of infections, and HLA background all shape the immunodominance pattern (29). Additionally, patterns of T cell cytokine response among patients with a secondary DENV infection were associated with severe (51,52) or mild dengue (53,54). Although heterotypic antigens were addressed only in one of these studies (52), such observations may indicate involvement of cross-reactive T cells in the clinical manifestation of DENV infections.…”
Section: Protection Vs Immunopathologymentioning
confidence: 99%